http://ocw.mit.edu
6.013/ESD.013J Electromagnetics and Applications, Fall 2005
Fall 2005
November 3, 2005
I. TM Solutions
From Electromagnetic Field Theory: A Problem Solving Approach, by Markus Zahn, 1987. Used with permission.
=0
y
(xd) ej(tkz z)
x d
Re
A2 e
j(tk
z)
z
Ez (x, z, t) =
Re
(A1 sin(kx x) + B1 cos(kx x)) e
x d
+(x+d) j(tkz z)
x d
Re A3 e
e
kx2 + kz2 = 2
(in dielectric)
2 + kz2 = 2 0 0
(xd)
A2 e
z (x) = A1 sin(kx x)
E
A2 e(x+d)
xd
x d
x d
Ex jkz E
z = 0
E
x
jk
(xd) x > d
z
A2 e
x =
jkz A1 cos(kx x) x < d
E
k
jkxz
A2 e(x+d)
x < d
= H H
x = 0, H
z = 0
E
t
z
1
E
y =
x
H
jkz E
j
x
j
(xd) x d
0
A2 e
=
j
kx A1 cos(kx x) x d
0 A2 e(x+d)
x d
Boundary Conditions
Ez (x = d+ ) = Ez (x = d ) A1 sin(kx d) = A2
0
j
j
Hy (x = d+ ) = Hy (x = d )
+
A2 = + A1 cos(kx d)
kx
A1
1
kx 0
0 kx
=
=
=
tan(kx d)
A2
sin(kx d)
cos(kx d)
+ 2 0 0 = 2 2 =
(n/d)2
, n = 1, 2, 3, . . .
0 0
(xd)
B2 e
z (x) = B1 cos(kx x)
E
(x+d)
B2 e
xd
x d
x d
x
E
z = 0
jkz E
x
jk
(xd) x > d
z
B2 e
x =
jkz B1 sin(kx x)
E
x < d
jkxz
(x+d)
x < d
B2 e
2
j
(xd)
0
B2 e
j
y =
H
kx B1 sin(kx x)
j
(x+d)
0
B2 e
xd

x d
x d
Boundary Conditions
Ez (x = d+ ) = Ez (x = d ) B2 = B1 cos(kx d)
j0
j
Hy (x = d+ ) = Hy (x = d )
B2 =
B1 sin(kx d)
kx
B2
0 kx
= cos(kx d) =
sin(kx d) =
cot(kx d)
B1
0 kx
2
2
(2n+1)
2d
n = 0, 1, 2, . . .
0 0
II. TE Solutions
A. Odd Solutions
(xd)
A2 e
z =
A1 sin(kx x)
H
A2 e(xd)
xd
x d
x d
= Hx + Hz
Hx jkz H
z = 0
H
x
z
x
jk
(xd)
z
A2 e
x =
jkz A1 cos(kx x)
H
k
jkxz
A2 e(x+d)
=
E
E
x = 0, E
z = 0
H
t
y = jkz H
x Hz
jE
x
j
(xd)
0
A2 e
Ey = j
kx A1 cos(kx x)
j
(x+d)
0
A2 e
x>d
x < d
x < d
xd
x d
x d
Boundary Conditions
j
j
y (x = d+ ) = E
y (x = d )
E
A2 = A1 cos(kx d)
kx
Hz (x = d+ ) = Hz (x = d ) A2 = A1 sin(kx d)
A2
0 kx
= sin(kx d) =
cos(kx d) =
tan(kx d)
A1
0 kx
B. Even Solutions
z
H
x
H
y
E
(xd)
xd
B2 e
=
B1 cos(kx x) x d
B2 e(x+d)
x d
jk
(xd) x > d
z
B2 e
jkz
=
kx B1 sin(kx x)
x < d
jkz
(x+d)
x < d
B2 e
j
(xd)
0
xd
B2 e
j
=
kx B1 sin(kx x) x d
j0
B2 e(x+d) x d
j
j
y (x = d+ ) = E
y (x = d )
E
B2 = B1 sin(kx d)
kx
z (x = d+ ) = H
z (x = d ) B2 = B1 cos(kx d)
H
B2
0 kx
= cos(kx d) =
sin(kx d) =
cot(kx d)
B1
0 kx